2020
DOI: 10.37358/rc.20.9.8321
|View full text |Cite
|
Sign up to set email alerts
|

Direct Hydrogenation and Hydrotreating of Neat Vegetal Oil into Renewable Diesel Using Alumina Binder with Zeolite

Abstract: Hydrodeoxygenation of vegetal oil and methyl oleate studied using Pt and Pd supported with alumina-beta-zeolite (a-Al2O3-H-a) and comparing its performance with NiMo/a-Al2O3 and Pd/C in a semi-batch reactor, at 300 - 340 oC and 2.0 MPa. This study has used Pd and Pt on H-a zeolites with alumina binder as extrudate and it examines over triglycerides hydrogenolysis. Pd/C showed higher rate of deoxygenation and the selectivity of C18/C17 was higher for NiMo-S/a-Al2O3 and PdPt/a-Al2O3-H-a. PdPt/a-Al2O3-H-a enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As hydroisomerization requires a bifunctional catalyst, the β-zeolites are chosen based on their good balance between acid and metal functions, and Al 2 O 3 is used as a binder where the amount of zeolite influences the ratio of acid/hydrogenation activity [128]. It was reported that the optimum ratio of H-β zeolites and γ-Al 2 O 3 binder was 40:60 wt% in the hydrodeoxygenation of vegetal oil without sulfur feed substitution using Pd and Pt as catalyst [129]. Although the deoxygenation rate was better using Pd/AC, Pt-Pd/γ-Al 2 O 3 -H-β zeolites boosted the activity of hydrogenolysis and hydrogenation with the H 2 partial pressure as the key parameter for thermal decomposition of unsaturated triglycerides.…”
Section: Synthesis With Other Component(s)mentioning
confidence: 99%
“…As hydroisomerization requires a bifunctional catalyst, the β-zeolites are chosen based on their good balance between acid and metal functions, and Al 2 O 3 is used as a binder where the amount of zeolite influences the ratio of acid/hydrogenation activity [128]. It was reported that the optimum ratio of H-β zeolites and γ-Al 2 O 3 binder was 40:60 wt% in the hydrodeoxygenation of vegetal oil without sulfur feed substitution using Pd and Pt as catalyst [129]. Although the deoxygenation rate was better using Pd/AC, Pt-Pd/γ-Al 2 O 3 -H-β zeolites boosted the activity of hydrogenolysis and hydrogenation with the H 2 partial pressure as the key parameter for thermal decomposition of unsaturated triglycerides.…”
Section: Synthesis With Other Component(s)mentioning
confidence: 99%
“…The HDO of sunflower oil contains unsaturated double bonds of triolein, trilinolein, tripalmitin, and tristearin triglycerides in the sunflower oil. These higher level unsaturated triglycerides demand higher consumption of hydrogen on hydrotreatment i.e., HDO pathway [35][36][37][38][39][40].…”
Section: Hydroisomerisation Of N-octadecenementioning
confidence: 99%